MENCEGAH DAN MEMBERANTAS POTENSI ADANYA KORUPSI MELALUI PEMBERIAN PENDIDIKAN ANTI KORUPSI DI LEMBAGA PENDIDIKAN - Gusti Kadek Sintia Dewi (Universitas Pendidikan Ganesha, 2022)
This study aims to find out and also analyze how to prevent or eradicate the potential for corruption through the provision of anti-corruption education in educational institutions, both schools and tertiary institutions. The research studies studied used qualitative methods, where the discussion results were obtained from various sources such as books, journals, articles, etc. This research intends to increase or strengthen the values of anti-corruption education among young people, including in educational institutions. Where is the current problem of corruption in Indonesia does not end. There are various factors that cause corruption, namely personal human factors, family and community factors, economic and political factors and organizational factors. The point is that Anti-Corruption Education is a way of preventing corrupt behavior that can be started by instilling anti-corruption values in all individuals, including students as the younger generation who are responsible as the next generation of the nation.